MULTIKULTURALISME DALAM NOVEL BUMI MANUSIA KARYA PRAMOEDYA ANANTA TOER - Dara Windiyarti (Fakultas Sastra Universitas Negeri Malang, 2014)
The study aims to describe multiculturalism in the 9th edition of novel Bumi Manusia by Pramoedya Ananta Toer, published in 2002. Multiculturalism deals with the dominant and the dominated, the majority and the minority, and the ruling party and the controlled party in the context of a transnational community. In the novel, multiculturalism is represented by Nyai Ontosoroh, a part of Indonesian minority group, who in search of her identity crosses the bridge of ethnicity and cultural gap. The qualitative study employs multiculturalism theory in a literature review format. The data were analysed descriptively using the interpretative technique. The findings reveal that: (1) multiculturalism in the novel denotes: (a) the differences and inequalities between the native and the European, and (b) the humiliation and marginalization of the indigenous people; and (2) multiculturalism covers the issues of: (a) establishing identity and inter-cultural communication, and (b) conducting cross-cultural communication.